Measurement and QCD analysis of double-differential inclusive jet cross sections in proton-proton collisions at √s = 13 TeV - Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (Journal of high energy physics)
A measurement of the inclusive jet production in proton-proton collisions at the LHC at root s = 13TeV is presented. The double-differential cross sections are measured as a function of the jet transverse momentum p(T) and the absolute jet rapidity vertical bar y vertical bar. The anti- k(T) clustering algorithm is used with distance parameter of 0.4 (0.7) in a phase space region with jet p(T) from 97 GeV up to 3.1TeV and vertical bar y vertical bar < 2.0. Data collected with the CMS detector are used, corresponding to an integrated luminosity of 36.3 fb(-1) (33.5 fb(-1)). The measurement is used in a comprehensive QCD analysis at next-to-next-to-leading order, which results in significant improvement in the accuracy of the parton distributions in the proton. Simultaneously, the value of the strong coupling constant at the Z boson mass is extracted as alpha(S)(m(Z)) = 0.1170 +/- 0.0019. For the first time, these data are used in a standard model effective field theory analysis at next-to-leading order, where parton distributions and the QCD parameters are extracted simultaneously with imposed constraints on the Wilson coefficient c(1) of 4-quark contact interactions.